Composición de ácidos grasos en algunos alimentos fritos y aceites de fritura y factores relacionados, en un sector universitario de Medellín-Colombia (2014)
ABSTRACT: Frying conditions affect fatty acids proportion in fried foods. Objective: To determine the effect of frying conditions on fatty acid composition: saturated, monounsaturated, polyunsaturated, and trans fatty acid in fried food and frying oils. Materials and methods: 22 food samples and their frying oils were collected in 4 restaurants, 4 coffee shops, and 3 street stalls placed at universities in Medellín, Colombia. Fatty acids composition was determined by gas chromatography after the frying. Oil composition was associated with frying conditions. Results: Palm oil was used in 7 places, soya oil in 2 and a mixture of vegetable oils was used in another 2 places. In fried potatoes, palm oil increased saturated fatty acid content and reduced polyunsaturated fatty acid content (p<0,05). Soya oil had a greater polyunsaturated and trans fatty acid content, and a lower saturated content (p=0,05), in all cases. In oils, saturated fatty acid were associated with present solids (p=0,03) and TFA were associated with hours/usage/day (p=0,02) and presences of solids (p=0,04). Frying conditions were inappropriate. Conclusion: Fatty acid distribution in fried potatoes depends of oil used for frying. Poor frying conditions affect saturated and trans fatty acid content in oil.